E-Samsat and Motor Vehicle Taxpayer Compliance in The Perspective of Systematic Literature Review - Enggaryanti, Aloysia Heny (Universitas Dinamika, 2024)
This research aims to analyze various findings and comparisons related to the effectiveness of the e-samsat system in facilitating the vehicle tax payment process, as well as its impact on the level of tax compliance. The urgency of the research answers the strategic challenges of utilizing the e-samsat application in managing motor vehicle taxes and supporting the development of efficient and inclusive public services. Novelty of research by comparing perspectives across time, viewpoints, research trends that can have an impact on increasing taxpayer compliance. Systematic literature review method using Preferred Reporting Items for Systematic Reviews and Meta Analyses through collecting and evaluating various relevant literature. The results achieved show that e-samsat has great potential to improve taxpayer compliance by providing easier and more transparent access, and reducing administrative difficulties. In addition, this system provides convenience in terms of online payment and simplifies services and facilitates supervision to be more efficient and effective. Nonetheless, some technical and social challenges such as technological infrastructure and public awareness need to be considered to optimize the success of E-SAMSAT implementation. This research is expected to contribute to the development of technology-based taxation policies and improve motor vehicle taxpayer compliance in Indonesia.